Attention: the mechanisms of consciousness. - Posner, M I (1994)
A number of recent papers and books discuss theoretical efforts toward a scientific understanding of consciousness. Progress in imaging networks of brain areas active when people perform simple tasks may provide a useful empirical background for distinguishing conscious and unconscious information processing. Attentional networks include those involved in orienting to sensory stimuli, activating ideas from memory, and maintaining the alert state. This paper reviews recent findings in relation to classical issues in the study of attention and anatomical and physical theories of the nature of consciousness.